This I Believe - Taylor, Henry P. (Tufts Archival Research Center, 2006)
Henry Taylor, President of Taylor and Caldwell, explains his belief that everything operates based on the principals of certain laws, weather they be natural, physical, social, or religious and failure to adhere to these laws inevitably results in disfuntion and chaos; and the supreme law would be the law of God.